Sketch Out the Myth of Wisdom and Blessing of Islamic Boarding School - Syarif, Zainuddin; Gaffar, Abdul (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2019)
Boarding school culture is a part of Islamic social setting that acknowledges the differences of human